Multicentric reticulohistiocytosis in a Taiwanese woman with Sjögren syndrome - Lan-hsin Cheng; Ying-Yi Chiang (Wolters Kluwer Medknow Publications, 2016)
Multicentric reticulohistiocytosis is a rare, non-Langerhans cell histiocytosis characterized by specific skin lesions and destructive arthritis. Clinically, it generally presents with multiple reddish-brown papulonodules over the hands, face, and trunk. The associated destructive arthropathy tends to be severe, with 50% of patients developing arthritis mutilans. Approximately 25-30% of patients present with neoplasia. Coexisting autoimmune diseases are also commonly reported. Here we report the case of a 59-year-old Taiwanese woman with underlying Sjögren syndrome who presented with the typical skin manifestations of multicentric reticulohistiocytosis and early interphalangeal joint involvement. The patient later showed partial response to methotrexate treatment.